Sensitivity of Nafion Films to Organic Substances, Especially Ketones - Alfredo Marquez Lucero; Miguel Orozco; Nancy Navarro; Virginia Collins (Advances in Polymer Technology)
This work shows the possibility to employ sulfonated tetrafluoroethylene-based fluoropolymer-copolymer, commercially known as Nafion, as a sensible layer on sensors to detect organic solvents such as ketones. The detection and evaluation of ketone corpuses is very important for multiple applications on medicine, specially to detect and evaluate diabetes mellitus from the breath of patients. Nafion is a very stable copolymer, easily available and relatively inexpensive. This allows us to envision the possibility of having cheap and reliable sensors to detect vapors of these substances based on this copolymer. The main result of the present work is that Nafion can protonate gaseous ions from organic solvents, such as acetone and similar substances, which modify its electrical properties, presenting a differentiated behavior according to the chemical nature of these substances, which could lead to their identification, designing an electrical nose, because each behavior is a fingerprint of the substance to detect. Then, this material can be used in the design of electrical sensors, which can be inexpensive, reliable, and chemically stable, representing an excellent alternative to ceramic sensors.